Bombesin-Like Receptor 3: Physiology of a Functional Orphan. (September 2016) - Xiao, Cuiying; Reitman, Marc L.
Abstract : Bombesin-like receptor 3 (BRS-3) is an X-linked orphan Gq-coupled receptor that regulates food intake, metabolic rate, body temperature, heart rate, blood pressure, and insulin secretion. Most BRS-3 actions occur via the brain, through mechanisms including regulating sympathetic outflow. Ablation of Brs3 causes obesity, while synthetic agonists produce weight loss.